ON SATIRICAL COMMENTS: POLITICAL HUMOR OF INDONESIANS DEPICTED IN INSTAGRAM POSTS - Nugraha, Danang Satria (International Journal of Humanity Studies (IJHS), 2024)
This study explores the phenomenon of political humor within Indonesian society, focusing specifically on the expression of satirical comments through Instagram posts. Employing critical discourse analysis as the methodological framework, the study examines how Indonesian users utilize humor to comment on political events, figures, and ideologies in the digital realm. By analyzing a selected sample of Instagram posts, the study aims to shed light on the linguistic and discursive strategies employed by users to construct satirical commentary and investigate the underlying socio-political implications of such discourse. The study findings highlight the significance of satirical comments in shaping public opinion and fostering political dialogue within Indonesian society. It uncovers Instagram users' diverse strategies to express their discontent, promote alternative perspectives, and foster critical thinking through humor. The study identifies recurring themes, targets, and stylistic patterns in satirical comments, offering valuable insights into contemporary Indonesia's political discourse and collective sentiment. This study contributes to the existing literature on critical discourse analysis. It provides an in-depth analysis of the unique ways Indonesians engage in political satire through Instagram, elucidating the intricate relationship between language, humor, and political critique.